Pituitary adenoma with adipose tissue: A new metaplastic variant. Issue 4 (9th January 2017) - Caporalini, Chiara; Buccoliero, Anna Maria; Pansini, Luigi; Moscardi, Selene; Novelli, Luca; Baroni, Gianna; Bordi, Lorenzo; Ammannati, Franco; Taddei, Gian Luigi
Abstract : Pituitary adenomas are benign tumors representing approximately 15–20% of intracranial neoplasms. There have been few reports of metaplastic osseous transformation and about 60 cases of neuronal metaplasia in pituitary adenoma but adipose metaplasia has not been previously described in the English literature. Here we report a case of pituitary adenoma with metaplastic adipose tissue in a 58‐year‐old male patient. Histologically this case fulfilled the criteria of a non‐functioning pituitary adenoma, and moreover a central area of adipose tissue, made by mature adipocytes, and many tumor cells, containing fat droplet were evident. Lipomatous transformation of tumor cells in the CNS has been previously observed but, to the best of our knowledge, our case is the first pituitary adenoma with such change. The histogenesis of the adipose element in pituitary adenoma is not well understood, and could be a result of a metaplastic change or divergent differentiation from a common progenitor cell.